2016
DOI: 10.1111/are.12984
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between water exchange and settling tank as a method for suspended solids management in intensive biofloc technology systems: effects on shrimp (Litopenaeus vannamei ) performance, water quality and water use

Abstract: A comparison between water exchange and settling tank as a method for suspended solids management in intensive biofloc technology systems: effects on shrimp (Litopenaeus vannamei) performance, water quality and water use Abstract Biofloc systems rely on microbial processes in the water column to recycle animal waste products, reducing the need for water exchange. These increases biofloc concentration in the water and some form of removal is needed. An experiment was carried out to evaluate two management pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
2
19
0
5
Order By: Relevance
“…The high concentrations of SS and TSS can cause discomfort in fish such as the accumulation of organic matter in the gills, which affect oxygen diffusion and also growth (Hargreaves, 2006;Avnimelech, 2012;Arantes et al, 2017). In a study of Litopenaeus vannamei culture in biofloc, Arantes et al (2017) found that the use of a settler chamber promoted improved the zootechnical performance of shrimp, resulting in higher productivity, survival and final weight.…”
Section: Discussionmentioning
confidence: 99%
“…The high concentrations of SS and TSS can cause discomfort in fish such as the accumulation of organic matter in the gills, which affect oxygen diffusion and also growth (Hargreaves, 2006;Avnimelech, 2012;Arantes et al, 2017). In a study of Litopenaeus vannamei culture in biofloc, Arantes et al (2017) found that the use of a settler chamber promoted improved the zootechnical performance of shrimp, resulting in higher productivity, survival and final weight.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to deterioration of water quality which negatively affects the health and growth of cultured shrimp (Gaona, Almeida, Viau, Poersch, & Wasielesky, ; Ray, Lewis, Browdy, & Leffler, ). To periodically remove excess unutilised floc particles various strategies such as central drainage system (Avnimelech, ) and settling tanks (Arantes, Schveitzer, Magnotti, Lapa, & Vinatea, ; Ray, Dillon, & Lotz, ) have been advised, these demands added facility and expenditure apart from wastage of microbial floc generated by additional carbohydrate application.…”
Section: Introductionmentioning
confidence: 99%
“…La remoción de nitrógeno por medio de los tres sistemas señalados son diferentes en términos de la utilización del sustrato, biomasa bacterial generada y subproductos, por lo que en un cultivo intensivo de camarón con cero recambio, los tres sistemas pueden estar presentes y competir por el mismo sustrato. De esta forma, la habilidad para controlar la proporción de carbono a nitrógeno mediante la formulación del alimento balanceado, remoción de sólidos y adición de carbono orgánico determinará la estrategia de manejo para el tipo de sistema utilizado (Arantes et al, 2016).…”
Section: Introductionunclassified
“…The removal of nitrogen through the three appointed systems are different in terms of substrate use, bacterial biomass generated and subproducts, therefore, in an intensive shrimp culture with zero replacement, the three systems can be present and compete with the same substrate. Thus, the ability to control the proportion of carbon to nitrogen by the formulation of balanced feed, solid removal and addition of organic carbon will determine the management strategy for the type of system used (Arantes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation